2020
DOI: 10.3390/reprodmed1030016
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Reveals Downregulation of the Wnt Signaling Pathway in Human Dysmature Cumulus Cells as a Hallmark for Evaluating Oocyte Quality

Abstract: Background: Dysmature cumulus cells are lower fertilization rates and abnormalities in embryonic development compared to maturation cumulus cells. Morphological evaluation of cumulus–oocyte complexes (COCs) considered the possibility that differences may also be found in gene expression. Purpose: To identify hallmarks for evaluating oocyte quality by investigating gene expression patterns in human cumulus cells surrounding oocytes. Methods: Cumulus cells were obtained from the cumulus–oocyte complex of inferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Summarizing, the GSK3β inhibition suggests an increase in MII oocytes incompetent to develop to the blastocyst stage, that had an also increased β-catenin localization in the cumulus cells nuclei after maturation. Altogether, these characteristics exhibited by the CHIR group are similar to that previously shown in human in vivo matured oocyte uncapable to develop to embryos and referred as dysmature oocytes, a term also used describe their respective follicles (AKINO et al, 2020;KANG et al, 2022;LOBO;DIZEREGA;MARRS, 1985).…”
Section: This Work Investigated the Relation Of The Exossupporting
confidence: 70%
See 1 more Smart Citation
“…Summarizing, the GSK3β inhibition suggests an increase in MII oocytes incompetent to develop to the blastocyst stage, that had an also increased β-catenin localization in the cumulus cells nuclei after maturation. Altogether, these characteristics exhibited by the CHIR group are similar to that previously shown in human in vivo matured oocyte uncapable to develop to embryos and referred as dysmature oocytes, a term also used describe their respective follicles (AKINO et al, 2020;KANG et al, 2022;LOBO;DIZEREGA;MARRS, 1985).…”
Section: This Work Investigated the Relation Of The Exossupporting
confidence: 70%
“…In view of our developmental results, we considered a validation of effectiveness of the CHIR99021 in the COCs. Thus, a experiment using immunostaining for β-catenin, a canonical member of the Wnt signaling pathway and related to the GSK3β activity (AKINO et al, 2020;ASUNI et al, 2006), were performed in matured COC under 3 previously described conditions (CTL, CHIR and DKK1) and also in intact immature COCs immediately fixed after aspiration.…”
Section: Cumulus-oocyte Complex Suscept Gsk3β Modulators Treatmentsmentioning
confidence: 99%
“…The WNT signaling pathway plays an imperative role in normal ovarian function, fertility (9,19), and development of follicles (9,20), as well as during embryogenesis (21). Akino and colleagues (22) showed that the dysregulation of this pathway in cumulus cells can result in follicle atresia, a reduced fertilization rate, and abnormal embryogenesis. The Wnt/β-catenin pathway is initiated when a ligand binds to the low-density lipoprotein receptor-related protein 5/6 (LRP5/6) and the Frizzled receptor.…”
Section: Discussionmentioning
confidence: 99%
“…WNT5A is a crucial mediator of the Hedgehog and Wnt signaling pathways that may regulate the formation of primordial germ cells. Akino et al showed that the transcription levels of WNT9B/WNT10B/ Frizzled-7/ AXIN2 , which are involved in the Wnt signal/β-catenin pathway, were significantly lower in human dysmature CCs than in control cells ( 27 ). Habara et al revealed that Wnt signaling is pivotal for primordial follicle activation due to regulation of the differentiation of pre-granulosa cells and subsequent oocyte maturation, which is another indicator of how Wnt signaling exerts an effect on oocyte quality and subfertility ( 28 ).…”
Section: Discussionmentioning
confidence: 99%